THE ROLE OF COMMUNITY INSTITUTIONS IN THE FRAMEWORK OF RESIDIVITY DEVELOPMENT FOR INFORMED CITIZENS IN CILEGON CLASS II A COMMUNITY INSTITUTIONS - Muhammad Nasir (International Journal Labs, 2024)
The role of social institutions in the context of developing prisoners in prisons, especially Cilegon prisons, needs to be increased so that the Binaa residents, after they have finished serving as prisoners, when they are released, have truly become good human beings in the community. Both from a religious and moral perspective and obeying legal regulations. The aim of this research is to determine the role of Cilegon Prison in the context of developing citizens in Class II Cilegon Correctional Institutions. The research method uses a quantitative descriptive approach with data analysis using descriptive statistics. The instrument used in this research is the researcher, who acts as a